1995
DOI: 10.1002/mds.870100609
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism and dilatation of the perivascular spaces (État Criblé) of the striatum: A clinical, magnetic resonance imaging, and pathological study

Abstract: Two men, 89 and 83 years of age, presented with predominantly axial parkinsonian signs. In both cases, magnetic resonance imaging of the brain showed numerous small foci, delineating the striatum. The lesions had the same signal as cerebral spinal fluid in both T1 and T2 sequences. Postmortem examination of the brain showed numerous lacunes due to dilatation of the perivascular spaces, frequently associated with alterations of the surrounding brain parenchyma. Typical changes of Parkinson's disease were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 12 publications
2
35
1
3
Order By: Relevance
“…A special MR imaging change of cribriform cavities in the BG was the feature of this group. An "état criblé" or "status cribrosum" has been previously proved to be multiple dVRS in pathologic studies 19 and has been reported only among cases of vascular Parkinsonism, 20 subcortical ischemic vascular dementia, 21,22 or CADASIL 23 but has not been reported in the general population, to our knowledge. The present data further emphasize that the accumulation of multiple dVRS is not rare and can occur in elderly people in the absence of severe disability or dementia.…”
Section: Discussionmentioning
confidence: 77%
“…A special MR imaging change of cribriform cavities in the BG was the feature of this group. An "état criblé" or "status cribrosum" has been previously proved to be multiple dVRS in pathologic studies 19 and has been reported only among cases of vascular Parkinsonism, 20 subcortical ischemic vascular dementia, 21,22 or CADASIL 23 but has not been reported in the general population, to our knowledge. The present data further emphasize that the accumulation of multiple dVRS is not rare and can occur in elderly people in the absence of severe disability or dementia.…”
Section: Discussionmentioning
confidence: 77%
“…Parkinsonizm olgularında etyolojide rol oynadığı ya da tesadüfen mi VRB gözlendiği bilinmemektedir, ancak ganglionları kortekse bağlayan subkortikal bölgelerde yoğunlaştığında VRB'lerin vasküler parkinsonizme yol açabileceği bildirilmiş yayınlar mevcuttur (5,14). Demans ve VRB ilişkisi ise daha az tartışılmış bir konudur.…”
Section: Discussionunclassified
“…Genişlemiş VRB'ler; hemen her yaş grubunda gözlenebilir ve sıklıkla bazal gangliyonlarda, sentrum semiovalede, mezensefalon ve subkortikal beyaz cevher bölgelerinde gösterilmiştir. Bu genişlemiş boşluklar yaşlanma, parkinsonizm, hipertansiyon, küçük damar hastalıkları ve hidrosefali ile ilişkilendirilmiştir, ancak parkinsonizm ve demans ile ilgili yayınlanmış olgular ve çalışmalar sınırlıdır (3)(4)(5) …”
Section: Introductionunclassified
“…In particular, the nigrostriatal dopaminergic nerve terminals within the striatum are highly vulnerable to ischemia [11], and the concentration of L -dopa is reduced in the cerebrospinal fluid from patients with suspected VP as well as IPD [63]. This may in part explain the initial transient response to L -dopa in some present patients with SLP or CWMH without 4- to 6-Hz tremor and cogwheel rigidity and in reported cases with vascular lesions without evidence of coexistent IPD at autopsy [6, 15, 44]. On the other hand, parkinsonism in cases with CWMH may be produced through disconnection of the basal gray matter (corticostriatal and thalamocortical tracts) and cerebellum from the supplementary motor area [18]as has been assumed in cases with hydrocephalus [64, 65]and Binswanger’s disease [18, 66].…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is variation in responsiveness to L -dopa among cases with IPD and other parkinsonian syndromes. L -Dopa-responsive cases with vascular lesions in the absence of pathological changes in the SNpc [15]and, conversely, L -dopa-unresponsive cases with pathological changes in the SNpc [44]have been reported. Third, IPD symptoms may possibly be modified by a few, small ischemic lesions [21, 45, 46].…”
Section: Discussionmentioning
confidence: 99%